RELATIONSHIP BETWEEN GENERATIONAL DIFFERENCES AND EMPLOYEE RETENTION IN KENYAN TELECOMMUNICATIONS FIRMS - D.A., Ogolla; H., Kidombo; T.A., Senaji (International Journal of Research -GRANTHAALAYAH, 2018)
Employee retention is a major challenge facing many organizations today. The understanding of Generational differences at the workplace has been identified as a key requirement in implementing measures for effective employee retention. Within the telecommunications firms in Kenya, the problem of employee retention is a major challenge to the telecommunications firms. This paper thus examines the effect of generational differences on the retention of engineers in telecommunications firms in Kenya from the generational theory and generational cohorts theory perspective. This study used the cross-sectional and descriptive survey research design. Data were analyzed using descriptive and inferential statistics. We found that there exist a statistically significant variation in employee retention across the generational cohorts as observed through employee engagement, job satisfaction and organizational commitment (continuance commitment, affective commitment and normative commitment). These findings extend the theory regarding employees’ retention and have implication for employee retention practices which should be differentiated across the generational cohorts.